Contemporary protectionism-causes and consequences - Grubacic, Sanja; Schuster, Julian (The Business & Management Review, 2019)
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Performance of State-Owned Enterprises: A Comparative Analysis of Ethiopian Airlines and Ghana Airways - Andoh, Samuel K.; Gebremariam, Yilma; Thorson, James; Bodo, Peter (American Journal of Management, 2019)
This paper examines the performance of two state-owned airlines: Ethiopian Airlines and Ghana Airways. While Ethiopian Airlines continues to operate successfully, the other airline has gone out of business. In an industry characterized by heavy competition and a high rate of failure, the success of the state- owned Ethiopian Airlines is intriguing. The evidence shows that Ethiopian Airlines outperforms the industry on some important benchmarks. These findings suggest that being a state enterprise is not necessarily a characteristic that leads to failure. Corporate culture and governance appear to be important factors in the success of Ethiopian Airlines.
Keywords: Airlines; Business And Economics--Management; Business metrics; Economic growth; Economic theory; Emerging markets; Failure; Profits; Public enterprise; Stockholders; Success; dept.eco; peer-reviewed; ⛔ No DOI found

Cohabitation before marriage? An examination of pre-acquisition alliance partnerships and merger outcomes - Yu, Han; He, Zhaozhao (Review of Quantitative Finance and Accounting, 2019)
Keywords: dept.eco; peer-reviewed

Attention on adolescent mental disorders: the long-term effects on labor market outcomes - Yu, Jia (International Journal of Applied Economics, 2019)
According to a presidential task force about national college health in 2005, 14.9% of college students have been diagnosed with depression or anxiety disorders. Almost 75% of them experienced mental health problems during their early childhood or adolescence. Specifically, this paper examines the longitudinal effects of learning disability and attention disorder, and behavior disorder, of children born in 1980 – 1984, on their labor market outcomes as young adults. This study applies data from the National Longitudinal Survey of Youth 1997 (NLSY97), which documents the transition from school to work, and from adolescence to adulthood. By applying a family fixed effects model with Heckman selection procedure and multinomial logistic regression, the research results show that experiencing mental health illness during childhood is associated with a decreased risk of employment, an increased risk of unemployment, and decreased weekly paid working hours. This effect is strong and significant for males, and barely discernible for females. Hence, childhood mental disorder is an important determinant of individual’s labor market outcomes. Targeting the improvement for boys’ mental illness situation might be beneficial for improving their labor market participation.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Are hedge fund returns affected by media coverage of macroeconomic news? - Dutta, Sandip; Thorson, James (Studies in Economics and Finance, 2019)
Purpose: Extant literature suggests that the difficulty associated with the interpretation of macroeconomic news announcements by the market in general in different economic environments, might be the reason why most studies do not find any significant relationship between real-sector macroeconomic variables and financial asset returns. This paper aims to use a different approach to measure macroeconomic news. The objective is to examine if a different measure of a macroeconomic news variable, constructed from media coverage of the same, significantly affects hedge fund returns. Design/methodology/approach: The authors use a news index for unemployment, which is a real-sector variable, constructed from newspaper coverage of unemployment announcements and examine its impact on hedge fund returns. Findings: Contrary to the other studies that examine the impact of macroeconomic news on hedge fund returns, the authors find that media coverage of unemployment news announcements significantly affects hedge fund returns. Practical implications: Overall, this paper demonstrates that the manner in which the market interprets macroeconomic news announcements in different economic environments is probably a more relevant factor for hedge funds and is more likely to impact hedge fund returns. In conjunction with variables – constructed from media coverage of unemployment news announcements – that factor in the manner of interpretation, it is found that surprises also matter for hedge fund returns. This is an important consideration for hedge fund managers as well. Originality/value: To the best of the authors’ knowledge, this is the first study that examines the impact of media coverage of macroeconomic news announcements on hedge fund returns and finds significantly different results with real-sector macro variables. © 2019, Emerald Publishing Limited.
Keywords: Finance; Financial economics; dept.eco; dept.fin; peer-reviewed

Estimation of a production function for Philippine retail stores - Patalinghug, Jason C. (Economics, 2019)
Abstract The purpose of this paper is the estimation of a production function for retail stores in the Philippines. A generalized Cobb-Douglas production function is utilized for this purpose. Ordinary Least Squares is used in obtaining the coefficients for labor and capital. The results show that the marginal product of labor to be higher than the marginal product of capital and the hypothesis of constant returns to scale is not rejected.
Keywords: dept.eco; peer-reviewed

What does improved spectrum management mean for the Philippines? - Patalinghug, Epictetus; Patalinghug, Jason (Annals of the Constantin Brancusi University of Targu Jiu, Economy Series, 2019)
This paper analyzes spectrum management practices in the Philippines. The regulatory body allocates available spectrum via an administrative approach which lacks transparency and due process. The paper recommends that the regulatory body adopts the auction method in allocating spectrums which is more transparent, fair, and cost-effective if a suitable design is adopted.
Keywords: Allocation Methods; Auction; Philippines; Spectrum Management; dept.eco; ⛔ No DOI found